The In Vitro and In Vivo Effects of Hypoxis hemerocallidea on Indinavir Pharmacokinetics: Modulation of Efflux - Havenga, Kaylee; Abay, Efrem; Wiesner, Lubbe; Viljoen, Alvaro; Steyn, Dewald; Hamman, Josias (Planta Medica, 2018)
Hypoxis hemerocallidea (African potato) is a popular medicinal plant that has been used traditionally for the treatment of various disorders. Some HIV/AIDS patients use this traditional medicine together with their antiretroviral therapy. This study aimed to determine the impact of selected H. hemerocallidea materials (i.e., a commercial product, an aqueous extract, and biomass reference plant material) on the bidirectional permeability of indinavir across Caco-2 cell monolayers as well as the bioavailability of indinavir during an acute, single administration study in Sprague-Dawley rats. All of the selected H. hemerocallidea test materials demonstrated inhibition effects on indinavir efflux across Caco-2 cell monolayers, albeit to different extents. An increase in the bioavailability of indinavir was obtained in vivo when administered concomitantly with the H. hemerocallidea materials, albeit not statistically significantly. The change in bioavailability directly correlated with the in vitro permeability results. It can therefore be concluded that the change in permeability and bioavailability of indinavir was caused by efflux inhibition and this effect was dependent on the type of H. hemerocallidea material investigated, which was found to be in the following order: commercial product > aqueous extract > reference plant material. The clinical significance of the combined effect of efflux and metabolism inhibition by H. hemerocallidea should be determined in another in vivo model that expresses the cytochrome P450 3A4 enzyme.
Keywords: Hypoxis hemerocallidea; Hypoxidaceae; herb-drug pharmacokinetic interactions; HIV; indinavir; traditional herbal medicines; efflux